2022
DOI: 10.1371/journal.pone.0276019
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of transcatheter edge-to-edge mitral valve repair in patients with diabetes mellitus: Results from a real-world cohort

Abstract: Background There are only limited data on patients with diabetes undergoing transcatheter edge-to-edge repair (TEER) in real-world settings. Previous data indicated patients with diabetes to have a worse prognosis. This study sought to evaluate safety and efficacy of TEER in patients with diabetes in a real-world cohort. Methods In this monocentric study 340 consecutive patients with severe primary and secondary mitral regurgitation (MR) undergoing TEER were included. Immediate results of the procedure, intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Renal disease was more frequent in their study in diabetics (65.1% vs. 51.9%; p = 0.002), while being balanced equally in our study (75.5% vs. 77.0%; p = 0.678) among FMR patients. Nevertheless, an overall greater comorbidity burden was seen among diabetics in our study, an observation also made by COAPT investigators [5] and others [14]. Apart from that, evidence regarding the outcome of diabetics after M-TEER is scarce: In a study by Hellhammer et al, diabetes independently predicted NT-proBNP non-response (≤30% decrease) at 6-month follow-up in a mixed cohort of 58 patients [19].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Renal disease was more frequent in their study in diabetics (65.1% vs. 51.9%; p = 0.002), while being balanced equally in our study (75.5% vs. 77.0%; p = 0.678) among FMR patients. Nevertheless, an overall greater comorbidity burden was seen among diabetics in our study, an observation also made by COAPT investigators [5] and others [14]. Apart from that, evidence regarding the outcome of diabetics after M-TEER is scarce: In a study by Hellhammer et al, diabetes independently predicted NT-proBNP non-response (≤30% decrease) at 6-month follow-up in a mixed cohort of 58 patients [19].…”
Section: Discussionsupporting
confidence: 65%
“…Across the field of structural cardiac [8][9][10] and coronary interventions [11][12][13], ample evidence has been provided linking diabetes mellitus to adverse outcomes. In patients treated with M-TEER, a subgroup analysis from the COAPT (Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients with Functional Mitral Regurgitation) trial suggests worsened survival in diabetics with FMR [5], whereas others did not find a significant impact of diabetes on outcomes after M-TEER [14,15]. Given the conflicting evidence, we further investigated the impact of diabetes in >1000 patients undergoing M-TEER.…”
Section: Introductionmentioning
confidence: 99%
“… 22 However, three other studies including 1,118, 340, and 58 patients, respectively, found that diabetes was not related to poorer outcome in those receiving transcatheter edge-to-edge mitral valve repair. 23 , 24 , 25 Extending to these studies, the present analysis included a total of 2,943 patients with isolated significant MR regardless of therapeutic strategy, and demonstrated that diabetes was independently associated with a 35% higher risk of two-year adverse events, and thus deserved particular attention in clinical practice. Given that diabetes was a well-established risk factor of perioperative mortality in patients undergoing valvular surgery and accumulating evidence confirmed the safety and efficacy of transcatheter mitral valve intervention in patients with diabetes, 25 , 26 , 27 , 28 the latter option may be more appropriate in carefully selected diabetic patients with clinically significant MR to improve long-term survival as well as the quality of life.…”
Section: Discussionmentioning
confidence: 78%
“…After adjusting for clinical characteristics and echocardiographic findings, diabetes was an independent predictor of two-year outcome in patients with significant MR. Several previous studies investigated the impact of diabetes in patients with mitral valve dysfunction, yet not yielded consistent results. 22 , 23 , 24 , 25 For instance, in an analysis of the Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients with functional Mitral Regurgitation (COAPT) trial, individuals with diabetes (229/614) suffered a significantly higher mortality rate than non-diabetic patients, and had a numerically higher rate of heart failure hospitalization. 22 However, three other studies including 1,118, 340, and 58 patients, respectively, found that diabetes was not related to poorer outcome in those receiving transcatheter edge-to-edge mitral valve repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation